Antidiabetic and Pharmacokinetic Properties of Shorea macrophylla Fruits’ Extracts in Borneo - Kristene Ling, Yong; Chung, Hung Hui; Melinda Lau, Mei Lin; Ivy Chew, Yee Yen; Crystal Lim, Jia Jing; Hew, Pei Xuan; Sim, Siong Fong (Universiti Putra Malaysia Press, 2025)
The global rise in diabetes prevalence has intensified the search for effective and safer natural antidiabetic agents. Shorea macrophylla fruits, known for their lipogenesis effects, present a promising avenue. This study explores the antidiabetic properties of S. macrophylla fruits’ crude extracts through in vitro assays for α-amylase and advanced glycation end-products (AGEs) inhibition, alongside molecular docking for inhibitor prediction and in silico pharmacokinetic evaluation. While all extracts exhibited mild inhibitory effects on α-amylase, they are significantly less effective than acarbose. Methanolic (MeOH) extract demonstrated the strongest inhibitory effects on AGEs, surpassing other extracts at 100 µg/ml. However, it exhibits no significant differences compared to Aminoguanidine (AG), suggesting its potential to become an alternative antiglycation source. Molecular docking revealed that five compounds, methyl stearate, methyl palmitate, methyl arachidate, methyl oleate, and methyl linoleate, had higher binding energies than acarbose for Human pancreatic alpha-amylase (HPA) (PDB ID: 5E0F). However, their binding energies with the receptor for advanced glycation end-products (RAGE) (PDB ID: 3O3U) were lower than AG (-3.515 kcal/mol), ranging from -5.760 to -6.510 kcal/mol with amino acid residue ARG-66 consistently involved in hydrogen bonding interactions. Analysis of pharmacokinetic properties confirmed that these compounds adhere to Lipinski’s Rule of Five, indicating their drug-like properties despite generally poor solubility and potential skin irritation. In summary, S. macrophylla fruits’ crude extracts, particularly the MeOH extract, show promise as antiglycation agents, necessitating further in vivo studies to validate these findings for drug development.